Aktivitas Antibakteri dan Uji Fitokimia Senyawa Metabolit Sekunder dari Limbah Kulit Pisang Kepok (Musa acuminata x balbisiana), Kulit Pisang Uli (Musa Paradisiaca Sapientum), dan Kulit Pisang Nangka (Musa sp L) - Andi Nursanti; Irma Herawati Suparto; Tetty Kemala (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
The study aimed to determine the secondary metabolites contained in raw banana peel waste, and to test the inhibitory activity in bacteria. Banana skin waste is used namely; banana kepok (Musa acuminata x balbisiana), uli banana (Musa paradisiaca sapientum) and nangka banana (Musa sp L) extracted using distilled water with the dekok method. The phytochemicals and antibacterial activity were tested for Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Phytochemical test results showed the three banana peel extracts contain the same compounds, namely alkaloids, flavonoids, saponins, tannins and phenols. Different content of kepok banana peel extract is triterpenoid compounds which are not possessed by uli banana peel extract or banana jackfruit extract. The higher the concentration of extract used, the greater the inhibitory power of the bacteria. Antibacterial test results showed that 25% concentration of uli banana peel had the best antibacterial inhibition on S. aureus bacteria compared with kepok banana peel extract and jackfruit banana could not inhibit the growth of E. coli bacteria.